An assessment of cancer clinical trials vocabulary and IT infrastructure in the U.S. - Gwaltney, K. (American Medical Informatics Association, 2001)
Twenty-three cancer research centers in the U.S. were assessed to determine data standards, vocabularies, and information infrastructure used in support of clinical trials. Eighteen of the 23 responded. Major findings were related to: 1) clinical trials infrastructure information, 2) current systems environment, 3) technical details, and 4) vocabulary and data standards. The size of the facility correlated with the quality, features and functionality of the clinical trials system (CTS). One facility had as many as 22 separate CTS. There were only 2 sites that had integrated clinical information systems (CIS) with CTS. The responses included the major vocabularies and data standards used in CTS. The majority used some automation but many also reported manual data entry. CTS had more manual entry than CIS because of regulatory reporting requirements. The assessment identified opportunities for guidance in defining vocabularies and standards for cancer clinical trial systems in the US.